The Content and Bioavailability of Mineral Nutrients of Selected Wild and Traditional Edible Plants as Affected by Household Preparation Methods Practiced by Local Community in Benishangul Gumuz Regional State, Ethiopia - Hailu, A.A.; Addis, G. (Hindawi Limited, 2016)
Edible parts of some wild and traditional vegetables used by the Gumuz community, namely, Portulaca quadrifida, Dioscorea abyssinica, Abelmoschus esculentus, and Oxytenanthera abyssinica, were evaluated for their minerals composition and bioavailability. Mineral elements, namely, Ca, Fe, Zn, and Cu, were analyzed using Shimadzu atomic absorption spectrophotometer. Effects of household processing practices on the levels of mineral elements were evaluated and the bioavailability was predicted using antinutrient-mineral molar ratios. Fe, Zn, Ca, Cu, P, Na, and K level in raw edible portions ranged in (0.64 ± 0.02–27.0 ± 6.24), (0.46 ± 0.02–0.85 ± 0.02), (24.49 ± 1.2–131.7 ± 8.3), (0.11 ± 0.01–0.46 ± 0.04), (39.13 ± 0.34–57.27 ± 0.94), (7.34 ± 0.42–20.42 ± 1.31), and (184.4 ± 1.31–816.3 ± 11.731) mg/100 g FW, respectively. Although statistically significant losses in minerals as a result of household preparation practices were observed, the amount of nutrients retained could be valuable especially in communities that have limited alternative sources of these micronutrients. The predicted minerals’ bioavailability shows adequacy in terms of calcium and zinc but not iron.